Comparative analysis of serum calcium, phosphorus, and vitamin D levels in pre- and postmenopausal women: A nutritional correlation study - Dhungana, Arun; Tamang, Jagat Man; Chaudhary, Narendra Kumar; Tiwari, Kalpana (Journal of Biomedical Sciences, 2024)
Background: Serum calcium and vitamin D deficiencies are common among post-menopausal women, which can lead to osteoporotic fractures. Early detection of imbalances in serum calcium, phosphorus, and vitamin D can aid in providing proper treatment. This study compares serum calcium, phosphorus, and vitamin D levels between pre-menopausal and post-menopausal women and assesses their relationship with dietary calcium and sunlight exposure. Material and methods: A cross-sectional study was conducted at Kathmandu Medical College between February and April 2024. Using consecutive sampling, participants’ serum samples were analyzed with an automated analyzer, and Pearson’s correlation was calculated using SPSS version 21. Results: BMI was significantly higher in post-menopausal women (24.28 ± 0.49 kg/m2) than in pre-menopausal women (23.25 ± 1.722 kg/m2). Pre-menopausal women had higher serum calcium (9.18 ± 0.47 mg/dl) and vitamin D levels (23.03 ± 6.01ng/ml) than post-menopausal women (8.91 ± 0.43 mg/dl and 21.75 ± 5.86 ng/ml, respectively). Serum phosphorus was higher in post-menopausal women (4.19 ± 0.66 mg/dl) compared to pre-menopausal women (4.01 ± 0.54 mg/dl). Vitamin D levels in post-menopausal women positively correlated with calcium and dietary calcium intake but had an insignificant correlation with sunlight exposure and a negative correlation with phosphorus. Conclusion: The study concludes that post-menopausal women have higher BMIs and lower serum calcium and vitamin D levels. Regular monitoring of bone markers, dietary calcium and vitamin D intake, and increased sunlight exposure are recommended to enhance bone health in pre-menopausal and postmenopausal women.